2008
DOI: 10.1089/jwh.2007.0446
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Women Performing Vaginal pH Self-Testing

Abstract: Study participants could accurately measure vaginal pH through self-testing. Vaginal pH self-testing may be a convenient tool to help women determine whether they should use an over-the-counter (OTC) antifungal medication or go to a physician for diagnostic workup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…19 A number of studies have either questioned the role of infectious agents in chronic vaginal symptoms 20 or pointed to the importance of psychosocial factors in the etiology of vaginal symptoms. [21][22][23] Researchers in the field are exploring protocols based on pH testing, 17,24 selfcollection of samples, 25 and more accurate tests such as polymerase chain reactions. 26 It is also possible that vaginal symptoms often represent selflimited conditions.…”
Section: Discussionmentioning
confidence: 99%
“…19 A number of studies have either questioned the role of infectious agents in chronic vaginal symptoms 20 or pointed to the importance of psychosocial factors in the etiology of vaginal symptoms. [21][22][23] Researchers in the field are exploring protocols based on pH testing, 17,24 selfcollection of samples, 25 and more accurate tests such as polymerase chain reactions. 26 It is also possible that vaginal symptoms often represent selflimited conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Consumer testing for vaginal pH measurement has been developed and FDA approved for OTC use. Several studies have demonstrated that women were able to self-collect samples and understand package directions (Roy, Caillouette, Faden, & Roy, 2005), that women's interpretation of testing results correlated with physician readings (Kulp, Chaudhry, Wiita, & Bachmann, 2008;Strauss, 2005). According to Nyirjesy and Sobel (2005), the use of the pH testing enhances women's self-diagnostic abilities and could decrease inappropriate antifungal treatment by women in 50 percent of cases.…”
Section: Self-diagnosismentioning
confidence: 99%
“…In a study on self-reading of skin reactions following chickenpox vaccination, a 90% agreement was found, and the procedure was stated to be usable for routine vaccination assessment [20]. Other examples where self-reporting by patients have been found to be reliable are reading of a patch test for nickel allergy [21], scoring of hand eczema [22], and self-assessment of vaginal pH measurement [23,24]. In some medical fields, a more advanced progress in terms of self-reading has developed, for example self-reporting of blood pressure in patients with hypertension, for which implementation of the procedure has been reported to lead to increased use and reinforced preventive benefits [25,26].…”
Section: Introductionmentioning
confidence: 99%